Corporate responsibility and corporate misbehavior: are CSR reporting firms indeed responsible? - Christine Reitmaier; Wolfgang Schultze; Julia Vollmer (Review of Accounting Studies, 2024)
We investigate whether firms that proclaim a commitment to corporate social responsibility (CSR) by CSR reporting indeed internalize such a commitment and behave more responsibly. We analyze the association of the issuance and quality of voluntary CSR reports with the occurrence, number, and severity of corporate misbehaviors, both preceding and subsequent to CSR reporting. We find a significantly positive association of CSR reporting with our measures of prior and future misbehavior. The results are corroborated by a quasi-natural experiment around the Rana Plaza disaster where we find that the signatories of an accord for better working conditions have significantly higher prior and future misbehavior relative to non-signatories and firms unaffected by the exogenous shock. Our results are in line with legitimacy theory implying that, on average, the firms' proclaiming commitment to CSR is not a signal of internalized commitment but more likely serves greenwashing and impression management purposes.
Keywords: G18; G32; K38; K42; M41; M48; Q01; 650; Corporate social responsibility (CSR); Corporate misbehavior; CSR reporting; Real effects; Signaling theory; Legitimacy theory